How an emergency department is organized to provide opioid-specific harm reduction and facilitators and barriers to harm reduction implementation: a systems perspective - Sunny Jiao; Vicky Bungay; Emily Jenkins; Marilou Gagnon (BMC, 2023)
Abstract Background The intersection of dual public health emergencies-the COVID-19 pandemic and the drug toxicity crisis-has led to an urgent need for acute care based harm reduction for unregulated opioid use. Emergency Departments (EDs) as Complex Adaptive Systems (CASs) with multiple, interdependent, and interacting elements are suited to deliver such interventions. This paper examines how the ED is organized to provide harm reduction and identifies facilitators and barriers to implementation in light of interactions between system elements. Methods Using a case study design, we conducted interviews with Emergency Physicians (n = 5), Emergency Nurses (n = 10), and clinical leaders (n = 5). Nine organizational policy documents were also collected. Interview data were analysed using a Reflexive Thematic Analysis approach. Policy documents were analysed using a predetermined coding structure pertaining to staffing roles and responsibilities and the interrelationships therein for the delivery of opioid-specific harm reduction in the ED. The theory of CAS informed data analysis. Results An array of system agents, including substance use specialist providers and non-specialist providers, interacted in ways that enable the provision of harm reduction interventions in the ED, including opioid agonist treatment, supervised consumption, and withdrawal management. However, limited access to specialist providers, when coupled with specialist control, non-specialist reliance, and concerns related to safety, created tensions in the system that hinder harm reduction provision with resulting implications for the delivery of care. Conclusions To advance harm reduction implementation, there is a need for substance use specialist services that are congruent with the 24 h a day service delivery model of the ED, and for organizational policies that are attentive to discourses of specialized practice, hierarchical relations of power, and the dynamic regulatory landscape. Implementation efforts that take into consideration these perspectives have the potential to reduce harms experienced by people who use unregulated opioids, not only through overdose prevention and improving access to safer opioid alternatives, but also through supporting people to complete their unique care journeys.